Monitoring and control of meeting rooms through a supervisory system and dashboard - Goncalves, Diego Batista; Santos, Sara Dereste dos (Brazilian Journal of Production Engineering, 2023)
The present work proposes the application of a control and monitoring system for meeting rooms, in an emulated form, to validate the use of these technologies in corporate environments, helping managers, technicians and companies in the maintenance of these environments that, with the advent of the home office and collaborative spaces, are becoming increasingly important within companies. In this work, the IRIDIUM MOBILE software was used to create the supervisory system that acts as a controller and gateway, sending information to the Tago.IO platform, through the HTTP protocol, to create a graphical interface (dashboard) for the team Responsible for room maintenance. The RMC3 controller, from Crestron, was used to act as a Programmable Logic Controller in the system designed for the meeting room, controlling the Boolean variables that indicate the status of the equipment (monitor, projector, video matrix, air conditioning, curtains and lighting). The work allowed showing, in a clear and precise way, the use of equipment in a meeting room, where the end user can have an idea of ​​what is happening in the environment and proved to be effective in terms of updating time in the cloud, less than 0.5s.